L’archéologie enfermée dehors. Retour sur un malentendu français - Blaise Dufal (L'Atelier du CRH, 2010)
The project of historical anthropology makes history and archaeology meet within the notion of material culture. However real and fruitful, such an encounter has not truly modified epistemological representations of archaeology or the latter’s relation to history. While archaeology proved most prestigious at the end of the 19th century, the first generation of the Annales tended to leave it aside. Archaeology is still considered as a minor subject, only providing further knowledge without ever shaping interpretation. This is due to the intermediary position held by archaeology, halfway between nature and culture. But today, this hybrid social science of objects takes on the full dimension of interdisciplinary bricolage and may be considered as a model pattern for the concrete practice of historians’ relations to other human and social sciences.